Fungsi Dewan Rakyat Daerah Pada Pengawasan Penyelenggaraan Pelayanan Admnistrasi Dinas Kependudukan Dan Pencacatan Sipil Kabupaten Pasangkayu - Try Saldi; Andi Pangerang Moenta; Marwati Riza (Indonesian Journal of Criminal Law, 2022)
The Research objective to analyze the function of DPRD in supervising the administration of population administration and civil disability services in Pasangkayu Regency and its inhibiting factors. This research was conducted using the socio-legal method. The results of this study indicate that: (1) the supervision carried out by the DPRD of the Pasangkayu Regency has not been optimal in carrying out its functions and duties so that the community is less sure of the local government that carries out the implementation of public services, especially in the Population and Civil Registration Office of the Pasangkayu Regency. (2) the Population and Civil Registration Office of the Pasangkayu Regency has obstacles and obstacles such as the community still getting a lot of brokers, the geographical location of the area is very remote, the number of additional requirements for population administration and the lack of facilities and infrastructure to support population administration and civil registration services. also find the lack of public awareness of the importance of population data and civil dissolution. Tujuan penelitian menganalisis fungsi DPRD Pada pengawasan penyelenggaraan pelayanan administrasi kependudukan dan pencacatan sipil Kabupaten Pasangkayu dan Faktor- faktor penghambatnya. Penelitian ini dilakukan dengan menggunakan metode sosio legal. Hasil penelitian ini menunjukkan bahwa : (1) pengawasan yang di lakukan oleh DPRD kabupaten pasangkayu belum optimal dalam menjalankan fungsi dan tugasnya sehingga masyrakat kurang yakin terhadap pemerintah daerah yang melakukan penyelenggaraan pelayanan publik terkhususnya di dinas kependudukan dan pencatatan sipil kabupaten pasangkayu. (2) dinas kependudukan dan pencatatan sipil kabupaten pasangkayu terdapat hambatan dan kendala seperti masyrakat masih banyak mendapatkan calo, letak geografis daerah yang sangat terpencil, banyaknya syarat tambahan administrasi kependudukan dan masih minimnya sarana dan prasarana pendukung pelayanan administrasi kependudukan dan pencatatan sipil, selain itu di temukan juga kurangnya kesadaran masyarakat akan pentingnya data kependudukan dan pencacatan sipil.